PERANAN DOSEN DALAM PERSAINGAN INTERNASIONAL ERA MASYARAKAT EKONOMI ASEAN (Studi Analisis Normatif) - Halimatul Maryani (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Abstract In the globalization era of international competition, ASEAN members have participated in the agreement of ASEAN Economic Community to create a highly competitive single production-based market to promote equitable economic development for all member countries and to integrate them with the global community; consequently the impact will make the competition in every field increasingly tight, including in education. To achieve the target as members of ASEAN Economic Community, it is obligatory for them to increase the adequate human resources and to be daring in ASEAN free market competition. Then, a question "Who is Human Resource?" appears. From education point of view, one of these resources is the lecturer. Then, the lecturers should play a role because they are the human resources in education and it is very necessary to improve their competence. Therefore, the role of the lecturers is expected to improve the quality of a university, especially in the campus environment and at least to be equal to the quality of education with other ASEAN members. This becomes a challenge for the lecturer as well. Keywords: Role of Lecturer, International Competition, ASEAN Economic Community